The Role of Housing Finance Actors in Regenerating Delhi's Unauthorised Colonies: An Examination of State–Citizen– Market Boundaries. (November 2020) - Naik, Mukta; Kunduri, Eesha
Semi-formal settlements like Delhi's unauthorised colonies (UACs), which await regularisation by the state, are characterised by aspirations for housing improvements and enhanced property values. Frustrated by the rigid regulatory frameworks that operate in the binaries of legal/illegal, formal/informal, planned/unplanned and having limited influence over processes of regularisation, UAC residents use 'transversal logics' (Caldeira, 2017) to negotiate planning regimes, credit markets and local politics to improve housing, which become their 'action space' to meet aspirations for social mobility. This article investigates the role of finance and networks of credit in autoconstruction, with a focus on the work of market actors in navigating market–citizen and market–state boundaries, foregrounded against the relatively well-studied politics of state–citizen relations. It finds that landowners and housing finance institutions, as well as actors within them, navigate regulatory boundaries through innovative partnerships and creative workarounds, and by strategically deploying collective and individual identities. Even as cities like Delhi endeavour to become planned world-class utopias, a multitude of actors continue to reshape the city's peripheral landscapes through the assertion, dissolution and spanning of multiple boundaries—regulatory, individual–collective, state–citizen, citizen–market and state–market.